Karakterisasi Plastik Boidegradable dari Pati Onggok Singkong dan Nata De Coco - Zainal Arifin; Raswen Efendi; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Tapioca solid waste from the processing of tapioca still contains starch, which can be used as a raw material for making biodegradable plastic. The purpose of this study was to obtain the best formulation in the manufacture of biodegradable plastics from cassava starch and nata de coco. This research was carried out experimentally using a completely randomized design (CRD). The treatments in this research were the ratio of tapioca solid waste and nata de coco, which are ON1(95:5), ON2(90:10), ON3(85:15) and ON4(80:20) in 10 g biodegradable plastic formulations. The results showed that the tapioca solid waste and nata de coco had a significantly affected on thickness, water resistance, water vapor transmission, tensile strength, elongation, and. biodegradation timebut has no significant effect on thickness. The best treatment chosen was ON4 ratio of tapioca solid waste and nata de coco (80:20) having thickness of 0.15 mm, water resistance 80.56% s, water vapor transmission 9.14 (g/m2/hour), tensile strength of 4.16 MPa, elongation of 33.81%, and biodegradation for 6th days. Keywords : Biodegradable plastic,nata de coco, tapioca solid waste